Psikoedukasi Bullying pada Anak dan Remaja di Karawang - Martono, Sigit; Dwianing, Yola Nurhalizah; Dewi, Vanesa Kusuma; Afriyenti, Lenny Utama (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Bullying is a deliberate activity aimed at hurting and instilling fear through the threat of further aggression, creating terror rooted in an imbalance of power. This activity aims to provide psychoeducation to children and adolescents about bullying and its impact on mental health. The community service event was held in Mekarpohaci Village, Cilebar District, Karawang Regency, on November 16, 2024, involving 20 children and adolescents as participants. The method used in this activity was psychoeducation, consisting of four stages: assessment, planning, implementation, and evaluation. Several topics were covered, including the definition of bullying, types of bullying, signs of bullying, causes of bullying, the impact of bullying, and steps to address bullying. The results of the activity showed that the children and adolescents actively participated in this psychoeducation, leading to two-way interaction. The participants were able to understand the basics of bullying, recognize its forms or examples, comprehend its impacts, and understand the steps to address bullying.